2018
DOI: 10.1088/1361-648x/aab819
|View full text |Cite
|
Sign up to set email alerts
|

Electrically active induced energy levels and metastability of B and N vacancy-complexes in 4H–SiC

Abstract: Electrically active induced energy levels in semiconductor devices could be beneficial to the discovery of an enhanced p or n-type semiconductor. Nitrogen (N) implanted into 4H-SiC is a high energy process that produced high defect concentrations which could be removed during dopant activation annealing. On the other hand, boron (B) substituted for silicon in SiC causes a reduction in the number of defects. This scenario leads to a decrease in the dielectric properties and induced deep donor and shallow accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The geometric structure of 4H-SiC supercell shows that the relaxed Si-C bond distance is 1.89 Å, which is in agreement with previous results [30,31]. role in determining the energy of formation since a system that experienced more strain is likely to form with a relatively higher formation energy than a system that experienced less strain in the bond length by the participating atoms.…”
Section: Structural and Electronic Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The geometric structure of 4H-SiC supercell shows that the relaxed Si-C bond distance is 1.89 Å, which is in agreement with previous results [30,31]. role in determining the energy of formation since a system that experienced more strain is likely to form with a relatively higher formation energy than a system that experienced less strain in the bond length by the participating atoms.…”
Section: Structural and Electronic Propertiessupporting
confidence: 91%
“…The criteria for calculating the chemical potential for the B, N, C and Si atoms and their values where taken from Ref. [30].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The chemical potentials µ Si for Si, µ C for C, µ P for P and µ Al for Al should satisfy the stability condition for bulk SiC. The µ, the effective chemical potential of the constituent of the compound must satisfy the condition µ ≤ H f , where H f (0.62 eV from our calculation [26]) is the heat of formation. In a perfect stoichiometry growth, µ must be equal to zero.…”
Section: Computational Detailsmentioning
confidence: 97%
“…Several experimental [5,6,7,8,9,10,11,12,13,14,15,16,17] and theoretical [18,19,20,21,22] (most especially using the well known density functional theory) studies of point defects in 4H-SiC have been reported. Point defects such as substitution, interstitials, vacancy and defect-complexes (interstitial-complex, vacancy-complex or antisite) have been reported in literature [18,19,23,24,25,26]. Report on the nuclear transmutation proceeding under high energy doping of Si and SiC by P suggests that an n-type phosphorus doped layer induced radiation damage defects in SiC [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation